STABILITAS AKTIVITAS ANTIOKSIDAN EKSTRAK BEKATUL BERAS MERAH TERHADAP OKSIDATOR DAN PEMANASAN PADA BERBAGAI pH [Stability of Antioxidant Activity of Red Rice Bran Extract Subjected to Oxidator and Heating in Various pH] - I Wayan Rai Widarta1)*; I Wayan Arnata2) (Jurnal Teknologi dan Industri Pangan, 2014)
Rice bran is acknowledged as the highest nutritious part of rice grain as well as rich in bioactive phytochemicals. Coloured rices are reported as potent sources of antioxidants therefore are regarded as viable source of antioxidants for functional foods. The aim of this study was to extract the bioactive component of red rice bran, and further the component  was subjected to antioxidant activity and stability tests. The research design was a factorial randomized complete design with two factors. The first factor was the pH of the maceration that consisted of 3 levels, i.e. 1, 2.5, and 4. The second factor was the ratios of bran and solvent that consisted of 4 levels, namely: 1:4, 1:6, 1:8, and 1:10. Total phenol, total anthocyanin and antioxidant activity were measured. The results showed that extraction at the pH of 1 and under the optimized conditions of a material–solvent ratio of 1:10 (wt./vol.) produced the most potent extract. This treatment resulted in 5.45 mg/100 g of total anthocyanins, 743.51 mg/100 g of total phenolics, 92.19% of antioxidant activity, and 441.74 mg/L of IC50. Reduction of the antioxidant activities as a result of heating of the red rice bran extract was greater than that of oxidator.